Regulation of Secondary Cell Wall Development by Cortical Microtubules during Tracheary Element Differentiation in Arabidopsis Cell Suspensions - Oda, Yoshihisa (American Society of Plant Biologists, 2005)
Cortical microtubules participate in the deposition of patterned secondary walls in tracheary element differentiation. In this study, we established a system to induce the differentiation of tracheary elements using a transgenic Arabidopsis (Arabidopsis thaliana) cell suspension stably expressing a green fluorescent protein-tubulin fusion protein. Approximately 30% of the cells differentiated into tracheary elements 96 h after culture in auxin-free media containing 1 μm brassinolide. With this differentiation system, we have been able to time-sequentially elucidate microtubule arrangement during secondary wall thickening. The development of secondary walls could be followed in living cells by staining with fluorescein-conjugated wheat germ agglutinin, and the three-dimensional structures of the secondary walls could be simultaneously analyzed. A single microtubule bundle first appeared beneath the narrow secondary wall and then developed into two separate bundles locating along both sides of the developing secondary wall. Microtubule inhibitors affected secondary wall thickening, suggesting that the pair of microtubule bundles adjacent to the secondary wall played a crucial role in the regulation of secondary wall development.